Development of rural tourism in China: The tragedy of anti-commons - Wei, Xinyi; Hu, Qiuguang (Frontiers in Public Health, 2022)
The long-term goal of "healthy China 2030" leads a number of large health industry new business type with “tourism +” as the carrier, and gives birth to a combination of ecological health preservation with rural tourism as the industrial carrier and great healthy development as the ideological sustenance. Modern rural tourism gradually tends to build a large health industry system with “tourism +”, pension and medical industry as the core. However, the development of rural tourism presents the complexity of industry, environment, governance and coordination structure. In tourism development, due to the high dispersion and fragmentation of the property rights of the resource objects themselves, as well as the involvement of a large number of "atomic" property rights and other stakeholders, coupled with the lack of strong organization and leadership, it is easy to lead to the lack of full development and utilization of rich tourism resources in rural areas. It is difficult to realize the "rental value" contained in tourism resources, which leads to the tragedy of anti-Commons. According to the actual case of China, this paper excavates the occurrence mechanism of anti-Commons tragedy in the development of rural tourism. Sort out the difficult problems of the tragic governance of the anti-Commons in the current environmental development, and further explore the governance path of the anti-Commons tragedy. The purpose of the study is to optimize the development environment of rural tourism and build a healthy space suitable for industry, residence and tourism.